Effect of Cerium Oxide Nanoparticles on Myocardial Cell Apoptosis Induced by Myocardial Ischemia-Reperfusion Injury: Effect of Cerium Oxide Nanoparticles on Myocardial Cell Apoptosis - Zhao, Yudan; Yang, Yahan; Wen, Yishu; Zhao, Maolin; Dong, Yifei (Cellular and Molecular Biology, 2022)
This study was to provide a theoretical basis for effective treatment of myocardial ischemia-reperfusion injury (I/R injury) and explore the effect of cerium oxide (CeO2) nanoparticles on myocardial cell apoptosis induced by I/R injury. In this study, 50 healthy male Sprague Dawley (SD) rats were selected and divided into five groups according to the random table method: a sham operation group, an I/R group, a 1 - 10 nm CeO2 nanoparticle group (CeO2-1 group), a 10 - 25 nm CeO2 nanoparticle group (CeO2-2 group), and a 50 nm CeO2 nanoparticle group (CeO2-3 group). Rats in different groups were injected with phosphate buffer solution (PBS) and CeO2 nanoparticles with different diameters, respectively. The rat models of I/R injury were prepared to explore and analyze the superoxide dismutase (SOD) activity, malondialdehyde (MDA) content, glutathione peroxidase (GSH-Px) activity, and myocardial cell apoptosis of rats with I/R injury by CeO2 nanoparticles. The results showed that the cardiomyocyte necrosis, SOD activity, MDA content, GSH-Px activity, and apoptosis index of the three groups of rats injected with CeO2 nanoparticles were much better than those in the I/R group. The effects on SOD activity, MDA content, GSH-Px activity, and apoptosis index of cardiomyocytes in the CeO2-2 group were significantly better than those in the CeO2-1 and CeO2-3 groups, showing statistically great differences (P< 0.05); and effects on SOD activity, MDA content, and GSH-Px activity of cardiomyocytes in CeO2-1 group were better obviously than those in the CeO2-3 groups, showing statistically observable differences (P< 0.05). In addition, the difference between the CeO2-1 group and CeO2-3 on the apoptosis index of cardiomyocytes was not statistically remarkable (P> 0.05). It can be considered that the CeO2 nanoparticles can effectively alleviate the effects of myocardial I/R injury, showing reliable clinical significance.